Formulasi Sediaan Pelembab Ekstrak Buah Melon Orange (Cucumis melo L. var. reticulatus) Dalam Bentuk Krim - Mellisa Laura Mintoro; Farida Lanawati Darsono; Sumi Wijaya (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Environmental factors such as extreme sunlight may disrupt skin’s moisture balance and cause the skin to dry out. Therefore, skincare products such as moisturisers are highly needed. In this study, orange melon (Cucumis melo L. var. reticulatus) was added to increase the value of the moisturiser product. Orange melon contains sucrose as the moisturising substance and antioxidant substance which helps to normalize the skin. The extraction process was carried out using juicer. The fruit extract was used at 10% (FI), 20% (FII), and 30% (FIII). This study aims to know the impact of increasing orange melon extract concentration on the physical characteristics of cream and its moisturising effect and antioxidant activity as well as the best formula. The evaluations consisted of physical characteristics, moisturising effect, and antioxidant test with DPPH method. The statistical results showed that the increase in extract concentration significantly affect the physical characteristics (pH, viscosity, spreadibility, ease of removal, adhesivity) and moisturising effect of the creams. Increasing extract concentration would cause a significant increase in the moisturising effect of creams containing synthetic humectants. The best formula which fulfilled the requirements of physical characteristics and effectiveness test, while possessing antioxidant effect was F2 (20% orange melon extract).